Synthesis and Characterization of ZnO Semiconductor Nanoparticles with Annealing Temperature Variation for Dye Synthesized Solar Cell Application - Supu, Idawati; Aulia Fitrah Ramadhani; Bunga Tang; Haerul Ahmadi; Dewa Gede Eka Setiawan (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2024)
This study aims to make ZnO semiconductor nanoparticles using annealing temperature variations for dye synthesized solar cells, identify the structure and particle size and surface morphology using SEM-EDX and UV-VIS to determine the wavelength and absorbance values. In the gel-combustion method, three samples were made with varying annealing temperatures of 700â°C, 800â°C, and 900â°C, respectively. The annealing temperature variation shows the difference in SEM test results, where the higher the annealing temperature, the smaller the particle size. EDX test results show that ZnO has been formed. In the UV-VIS characterization results for the three samples have different transmittance values and wavelengths from samples without dye, ZnO doping chlorophyll. Based on XRD data, the higher the calcination temperature, the smaller the particle size, and the distribution of particle size at each increase in annealing temperature. Based on the results of SEM analysis obtained that the particle size is getting smaller with increasing annealing temperature.Â  According to the UV-Vis analysis results obtained that the addition of chlorophyll extract does not have a significant effect about wavelength 370 nm on the transmittance value of each sample, so the best absorbance is owned by the ZnO doping dye sample.